Reconstruction of Financial Reports Based on Isak No 35 at Nurul Huda Mosque in Prajekan Kidul Village, Bondowoso Regency - Umaroh, Dwi Dian Naefatul; Nuha, Gardina Aulin; Nastiti, Ari Sita (West Science Accounting and Finance, 2025)
The mosque is a non-profit organization that focuses on religious issues. The purpose of the mosque is not to profit from its activities. Although it is a non-profit organization, the mosque is still required to prepare an annual financial report. The purpose of this study was to determine how the financial recording and reporting were carried out by the management of the Nurul Huda Mosque and to determine the suitability of the preparation of the Nurul Huda Mosque financial report in accordance with ISAK No. 35. The method in this study was qualitative descriptive with a case study approach. The data analysis used consisted of four stages starting from data collection, data reduction, data presentation and drawing conclusions. The results of this study found that the Nurul Huda Mosque in the process of recording and reporting its finances by first making manual recordings, then re-recording using a computer. The financial report prepared by the treasurer currently only includes information related to income and expenses within a period of one month. The Nurul Huda Mosque has not been able to apply ISAK 35 in preparing its financial reports because it is constrained by inadequate human resources.